P388Reduced pressure overload-induced myocardial remodeling in K201-treated mice with the R4496C cardiac ryanodine receptor mutation. (15th July 2014) - Sedej, S; Matovina, M; Schmidt, A; Ljubojevic, S; Heinzel, FR; Negri, S; Napolitano, C; Vos, MA; Priori, SG; Pieske, B
Abstract: Purpose: Spontaneous sarcoplasmic reticulum (SR) Ca2+ release through defective cardiac ryanodine receptor (RyR2) promotes contractile dysfunction and myocardial remodeling in response to pressure overload. We tested the hypothesis that RyR2 stabilizer K201 attenuates the SR Ca2+ leak and ameliorates pressure overload-induced cardiac remodeling in mice carrying RyR2 gain-of-function mutation. Methods: RyR2R4496C+/- knock-in mice (R4496C) and their wild-type (WT) littermates underwent surgery without (Sham) or with transaortic banding (TAB). Changes in Ca2+ spark frequency (as a measure for the SR Ca2+ leak) were monitored by means of confocal Ca2+ imaging (Fluo-4/AM, linescan mode) in isolated ventricular cardiomyocytes (1 week post-surgery) under control conditions and after the pre-incubation (≥ 1-hour) with 300 nmol/L K201 or 1 mmol/L dantrolene (positive control). K201 (12 mg/kg/day) or DMSO (vehicle) was administered in R4496C-TAB mice for 4 weeks via osmotic minipumps. K201 plasma concentration was determined by using high performance liquid chromatography. Structural dimensions and function of the left ventricle (LV) were assessed by transthoracic echocardiography 1 and 3 weeks after surgery. Data are shown as mean±S.E.M. Results: K201 markedly reduced the increase in Ca2+ spark frequency at matched SR Ca2+ load in R4496C-TAB (83.9±8.6 pL-1s-1 vs. 332.7±42.9 pL-1s-1) and WT-TAB cells (82.2±6.5 pL-1s-1 vs. 190.1±27 pL-1s-1) as well as R4496C-Sham cells (72.1±7.5 pL-1s-1 vs. 173.6±20.9 pL-1s-1, all P<0.05 versus control, respectively). The RyR2 stabilizing effect was more pronounced in the presence of K201 than dantrolene. Chronic infusion of K201 resulted in a mean K201 plasma concentration of 163±25 nmol/L. In R4496C-TAB mice, K201 prevented the decline in fractional shortening (1 week: 24.5±2.6% vs. 17.9±1.8%; 3 weeks: 21.3±2.6% vs. 15.2±2.4%, both P<0.05 versus vehicle-treated R4496C-TAB, respectively), restored an increase in the relative wall thickness (1 week: 0.44±0.02 mm vs. 0.40±0.01 mm; 3 weeks: 0.46±0.02 mm vs. 0.36±0.03 mm) and largely ameliorated LV dilatation (LV end-systolic diameter, 1 week: 3.10±0.15 mm vs. 3.75±0.26 mm; 3 weeks: 3.35±0.19 mm vs.4.23±0.31 mm, all P<0.05 versus vehicle-treated R4496C-TAB, respectively). K201 treatment reduced mortality over 6 weeks after TAB: 83% of K201-treated R4496C-TAB mice were alive vs. 31% treated with the vehicle (P<0.05). Conclusions: Pharmacological stabilization of SR Ca2+ release by K201 ameliorates the development of heart failure, preserves systolic function and improves survival in R4496C-TAB mice.